#TITLE_ALTERNATIVE# - KUNCORO (NIM 15108030); Pembimbing: Dr. Irwan Meilano, ST, M.Sc dan Dr. Ir. Dina Anggreni Sars, HENRI
One of the GPS kinematic processing software that developed currently is RTKLIB. RTKLIB is the software which people may download and use it freely. This software can perform fast and real-time data processing. In this study, the ability of RTKLIB tested by using GPS observation data with variations of the baseline length when earthquake not occured and earthquake offset detection from the GPS baseline processing results during earthquake. In this testing the stability of the GPS data processing results are evaluated. It can be seen also the ability and reliability of the software in detecting earthquake offset. For comparison the quality of data processing results, in this studythe data also processed by using TTC (Trimble Total Control). From the results of GPS baseline processing with RTKLIB and TTC, it seems that RTKLIB results have better stability than TTC. In short baseline category, the standard deviation less than 1 cm, in medium baseline category the standard deviation between 3-6 cm, and in long baseline category the standard deviation is 3-8 cm. On the earthquake offset detection, RTKLIB have ability to detect offset in more of baseline length variations than the TTC.